2010
DOI: 10.1093/beheco/arq010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal yolk testosterone in canary eggs: toward a better understanding of mechanisms and function

Abstract: Maternal yolk androgens in avian eggs have been shown to affect numerous offspring traits. These changes in offspring phenotype represent examples of maternal effects and are thought to adjust offspring development to the posthatching environment. When studying the functional consequences of yolk hormones it is, therefore, crucial to manipulate the yolk androgen concentrations as well as the environmental conditions under which the study is performed. However, so far context-dependent effects of maternal yolk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 38 publications
6
49
1
Order By: Relevance
“…The results suggest that these chicks have a lower sensitivity to plasma testosterone, in line with the effect of yolk testosterone feminizing competitive behaviour , see also Rubolini et al 2006). However, in other species enhancing effects of yolk testosterone on androgen dependent behaviors/traits have been found (competitive behaviour: Eising et al, 2006;Müller et al, 2010;Partecke and Schwabl, 2008;Ruuskanen and Laaksonen, 2010;Schwabl, 1993;Strasser and Schwabl, 2004; nuptial plumage/secondary sexual traits Eising et al, 2006;Strasser and Schwabl, 2004; see also Müller and Eens, 2009). The latter suggests that yolk testosterone may increase the sensitivity to circulating plasma testosterone, since in some of these studies no increase in circulating plasma testosterone was found despite the fact that phenotypic changes were observed (e.g.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The results suggest that these chicks have a lower sensitivity to plasma testosterone, in line with the effect of yolk testosterone feminizing competitive behaviour , see also Rubolini et al 2006). However, in other species enhancing effects of yolk testosterone on androgen dependent behaviors/traits have been found (competitive behaviour: Eising et al, 2006;Müller et al, 2010;Partecke and Schwabl, 2008;Ruuskanen and Laaksonen, 2010;Schwabl, 1993;Strasser and Schwabl, 2004; nuptial plumage/secondary sexual traits Eising et al, 2006;Strasser and Schwabl, 2004; see also Müller and Eens, 2009). The latter suggests that yolk testosterone may increase the sensitivity to circulating plasma testosterone, since in some of these studies no increase in circulating plasma testosterone was found despite the fact that phenotypic changes were observed (e.g.…”
Section: Introductionsupporting
confidence: 57%
“…Soma et al, 2008 for a recent review and Sartor et al 2005 for evidence in canaries). Furthermore, aggression has been shown to be influenced by yolk testosterone, among other in our study species (Eising et al, 2006;Müller et al 2010;Partecke and Schwabl, 2008;Schwabl 1993;Strasser and Schwabl 2004; but see Müller et al, 2008;Ruuskanen and Laaksonen, 2010; Table 2). …”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Finally, the smaller structural size of nestlings may have been due to females in the enhanced plumage brightness treatment depositing a greater concentration of testosterone in the yolks of their eggs as a result of nest-site intrusions (Whittingham and Schwabl, 2002) since they likely experienced more frequent and aggressive challenges by naturally bright females of greater competitive ability (see Chapter 3). Although elevated yolk testosterone levels have been shown to enhance the growth of nestlings in some species (Eising et al, 2001;Müller et al, 2010), negative effects on nestling structural size have also been demonstrated (Sockman and Schwabl, 2000), and the effect of androgens on nestling development may depend on the concentration deposited by the female (Muriel et al, 2015). Unfortunately, the only way to distinguish whether the effect of plumage brightness treatment on nestling quality is due to the effects of androgen deposited in egg yolks or lower provisioning rates by females would be to cross-foster nestlings among the plumage brightness treatments so that nestlings were reared by females other than their genetic mother.…”
Section: Discussionmentioning
confidence: 99%